A comparison of three different cooling systems in parral type greenhouses in Almeria - Meca, D.=700 1 Lopez, J.C.; Gazquez, J.C.; Baeza, E.; Perez Parra J.; Zaragoza, G.
(En, Es)
Ilus., 26 ref.
Keywords: TRATAMIENTO TERMICO; BLANQUEO; INVERNADEROS; REFRIGERACION; ESPAÑA; PANTALLA DE SOMBREO